Parkinsonism in a recurrent cervical cancer patient: case report and review of the literature. - Afshin Azimirad; Zahra Sarraf (Tehran University of Medical Sciences, 2013)
A 49 year old woman diagnosed as a cervical cancer patient, after receiving appropriate treatment experienced metastasis in her abdominopelvic cavity. After aggressive management, she was well for a while. However, she developed to a poor condition consisting of urologic, gastroenterological, hematologic and neurologic problems just in a short time. In the course of hospital she presented one sided passive bradykinesia, resting tremor, cogwheel rigidity with controlateral suspicious CT scan of brain. She passed away soon after that.